A new species of Karualona Dumont & Silva-Briano, 2000 (Cladocera: Anomopoda: Chydoridae: Aloninae) from Northeast Thailand - Tiang-Nga, Supatra; Sinev, Artem Y.; Sanoamuang, Laorsri (Zootaxa, 2021)
A new species of Aloninae, Karualona arcana sp. nov. (Cladocera: Chydoridae) is described from Northeast Thailand. It differs from other species of the genus Karualona Dumont & Silva-Briano, 2000 by: (1) the inner distal lobe of limb I bearing two setae; (2) shape of the postabdomen; (3) setae on the apical segment of the antenna endopodite of equal thickness; and (4) the presence of setules on the anterior margin of labrum. Some morphological characteristics of this taxon do not match well with the genus diagnosis, but share several important characteristics as well, such as: (1) presence of two main head pores and minute lateral pores; (2) presence of a lateral indentation on labral plate; (3) presence of denticles on the posteroventral angle of valves; (4) two flaming-torch setae on endite of limb IV; and (5) lack of composite denticles on postabdomen.